2005
DOI: 10.1161/01.cir.0000153271.77341.9f
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Brain Natriuretic Peptide Predicts Blood Pressure Response After Stent Revascularization in Patients With Renal Artery Stenosis

Abstract: Background-A significant number (20% to 40%) of hypertensive patients with renal artery stenosis will not have blood pressure improvement after successful percutaneous revascularization. Identifying a group of patients with refractory hypertension and renal artery stenosis who are likely to respond to renal stent placement would be beneficial. Methods and Results-Brain natriuretic peptide (BNP) was measured in 27 patients with refractory hypertension and significant renal artery stenosis before and after succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 35 publications
3
58
2
2
Order By: Relevance
“…When the poststent BNP fell by Յ30%, only 1 patient (10%), had improved blood pressure control (PϽ0.001) ( Figure 5). 46 Our preliminary data suggest that BNP is increased in patients with refractory hypertension and renal artery stenosis and that this peptide may be useful in predicting which patients will clinically improve their blood pressure after successful renal revascularization. An elevated baseline BNP Ͼ80 pg/mL strongly correlated with hypertension improvement after 3.5 months of follow-up.…”
Section: Biomarkersmentioning
confidence: 78%
See 2 more Smart Citations
“…When the poststent BNP fell by Յ30%, only 1 patient (10%), had improved blood pressure control (PϽ0.001) ( Figure 5). 46 Our preliminary data suggest that BNP is increased in patients with refractory hypertension and renal artery stenosis and that this peptide may be useful in predicting which patients will clinically improve their blood pressure after successful renal revascularization. An elevated baseline BNP Ͼ80 pg/mL strongly correlated with hypertension improvement after 3.5 months of follow-up.…”
Section: Biomarkersmentioning
confidence: 78%
“…Preliminary data suggest that the use of physiological lesion assessment (renal FFR) and/or biomarkers (BNP) can enhance lesion selection and result in improved clinical response rates. 40,46 Further studies are needed to establish their clinical role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work suggests a relationship between brain natriuretic peptide and RAS, with high brain natriuretic peptide levels (Ͼ80 pg/mL) associated with better outcomes after renal artery intervention. 55 Angiotensin II, endothelin, or an insulin-like growth factor, and sympathetic activation all may be involved in the process of ventricular thickening and stiffening. 46 -49,53 Angiotensin has been implicated in the mechanism of cardiac hypertrophy and is known to induce protein synthesis in myocardial cells, 50 even when the mean arterial pressure is lowered.…”
Section: Ras and Cardiovascular Eventsmentioning
confidence: 99%
“…Previous investigators have suggested that the response to revascularization may be predicted by the presence of microvascular dysfunction measured with the renal resistive index 100 or by the presence of neurohumoral activation. 55 Fundamentally, though, each of these observations is limited by the absence of a contrasting group of medically managed patients who are concurrent and carefully controlled. Thus, all such observations suggest but are unable to establish the relative benefit of revascularization or the true value of the baseline test strategy to predict outcome with differing treatments.…”
Section: Limitations Of Nonrandomized Evidencementioning
confidence: 99%